2016
DOI: 10.1111/bcp.13079
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of tranexamic acid in hip fracture surgery

Abstract: AIMTo systematically examine and quantify the efficacy and safety of tranexamic acid in hip fracture surgery. METHODSA systematic literature search was conducted using Medline, EMBASE, AMED, CiNAHL, and the Cochrane Central Registry of Controlled Trials. Two assessors independently screened search outputs for potentially relevant articles which met the eligibility criteria. The primary outcome measure was requirement of post-operative blood transfusion. Risk of bias assessment was performed using the Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 40 publications
(64 reference statements)
4
57
1
Order By: Relevance
“…These events are not statistically signifi cant. Our results agree with those of the literature as shown by the systematic review by Farrow et al 28 and Mayeux et al 29 Tranexamic acid was administered before incision and not during or at the end of surgery so as not to greatly affect the blood loss, as proposed by Gaused et al 30 The dose used was 15 mg/kg, which differed from that used by Gaused (1g in 100 cc of saline solution). 30 The reduction in haemoglobin levels of the sample examined turned out to be statistically signifi cant, and the data are in line with the international literature.…”
Section: Resultssupporting
confidence: 90%
“…These events are not statistically signifi cant. Our results agree with those of the literature as shown by the systematic review by Farrow et al 28 and Mayeux et al 29 Tranexamic acid was administered before incision and not during or at the end of surgery so as not to greatly affect the blood loss, as proposed by Gaused et al 30 The dose used was 15 mg/kg, which differed from that used by Gaused (1g in 100 cc of saline solution). 30 The reduction in haemoglobin levels of the sample examined turned out to be statistically signifi cant, and the data are in line with the international literature.…”
Section: Resultssupporting
confidence: 90%
“…In our study, no statistically significant differences were found between the TXA and placebo groups for incidence of wound complications, thromboembolic events, or mortality after 6 months' follow-up (Table 3). Our results were in accordance with the systematic reviews of Farrow et al 38 and Zhang et al, 33 which indicated that TXA did not increase the risk of wound complications, thromboembolic events, or mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The total blood loss in the TXA group was reduced by 289 mL [138; 440 ml]. The same effect was observed in the meta-analysis of Farrow and colleagues(27). The rate of intra-and postoperative blood transfusions was significantly lower in the included randomized controlled trials (of seven studies with 750 patients).…”
mentioning
confidence: 71%
“…As for knee replacement surgery, the state of evidence for the intravenous application of TXA is very heterogeneous. Very different dosages were used in the published work; for instance, the randomized controlled trial included in the meta-analysis by Farrow et al investigated doses of 1-4 g/24 hours (27). Studies were included with and without chemical thrombosis prophylaxis.…”
Section: State Of Evidence For Hip Replacementmentioning
confidence: 99%